THE STUDY OF LANGUAGE DISORDER OF AN AUTISTIC SAVANT PORTRAYED IN LEVINSON’S RAIN MAN FILM (1988) - Resti Levia; Jufrizal Jufrizal; Leni Marlina (English Language and Literature, 2019)
ABSTRACT Autistic savant as one of the language disorders can be found in daily life and it also can be portrayed in literary works and films. An autistic savant is a person with autism who has the limitation in most social functions but has cognitive abilities, such as possessing some outstanding memories and computational skills. This research aims to find out the types of language disorder and to find out the dominant type of language disorders found in autistic savant portrayed in Levinson’s Rain Man film. This research used a descriptive method. The data used in this research were the utterances of an autistic savant. The result of this research shows that the type of expressive language disorder was obtained with the occurrence percentage of 67.7% while the receptive language disorder type was obtained by the occurrence percentage of 32.3%. From this percentage, it can be seen that the most dominant type of language disorders experienced by autistic savant in Rain Man film is expressive language disorder. It means the autistic savant as an adult person also has difficulty in expressing or producing language. Key words: language disorder, autistic savant, expressive language disorder, receptive language disorder